Evaluation of Flexibility Value Using Reflex Algebraic Model in Electrical Systems with Variable Generation - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2023)
Electricity generation has evolved from conventional systems that use resources such as coal or oil, to renewable generation systems, using solar and wind energy. However, the variability of these resources can compromise the operational continuity of a system by making it difficult to assign secondary reserves necessary for the system, increasing the complexity in determining the flexibility recquired. The Renewable Energy FLEXibility (REFLEX) model, unlike others, internalizes the system s flexibility deficit as constraints in the unit commitment, allowing flexibility deficiencies to be economically valued when assigning reserves due to the high penetration of Variable Renewable Energy (VRE). Chilean electrical system is used as study case to verify the effectiveness of the model, finding an optimal economic relationship between the integration of VRE and the sizing of required reserves, allowing analysis on guidelines looking to keep systems flexible and reliable. © 2023 IEEE.